2010
DOI: 10.1001/archoto.2010.123
|View full text |Cite
|
Sign up to set email alerts
|

MUC5ACExpression in Human Middle Ear Epithelium of Patients With Otitis Media

Abstract: Objective Mucin gene 5AC (MUC5AC) has been identified as a major secretory mucin in the middle ear (ME). MUC5AC is fundamentally important in the development of ME mucoid effusions, hearing loss and also provides ME mucosal protection and bacterial clearance. The objective of this study is to compare levels of ME MUC5AC expression in patients with otitis media (OM) to patients without OM. Subjects Patients from 9 months to 7 years undergoing routine tympanostomy tube (TT) insertion for recurrent otitis media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 10 publications
2
25
0
Order By: Relevance
“…Among these, MUC2 , MUC5AC , and MUC5B have been shown to play an important role in the pathogenesis of OM. 4143 Abnormally high levels of mucin proteins have been demonstrated in middle ear effusions of CSOM patients. 44 This presence of mucin prevents the transmission of sound waves from the middle ear to the inner ear, hence leading to conductive hearing loss.…”
Section: Epithelial Cellsmentioning
confidence: 99%
“…Among these, MUC2 , MUC5AC , and MUC5B have been shown to play an important role in the pathogenesis of OM. 4143 Abnormally high levels of mucin proteins have been demonstrated in middle ear effusions of CSOM patients. 44 This presence of mucin prevents the transmission of sound waves from the middle ear to the inner ear, hence leading to conductive hearing loss.…”
Section: Epithelial Cellsmentioning
confidence: 99%
“…Otitis media is known to alter expression of selected cytokine [9], [11], mucin [12], tissue remodeling [11], and ion homeostasis genes [13] in the mouse middle ear (ME) and inner ear (IE). However, whole mouse genome studies of the gene expression in a setting of otitis media have not previously been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Kerschner et al [411] have reported MUC5AC as fundamentally important in the development of ME mucoid effusions, hearing loss that also provides middle ear (ME) mucosal protection and bacterial clearance. This demonstrates MUC5AC gene changes in patients with otitis media (OM) and highlights the need for greater understanding of the molecular responses in OM; particularly that of mucin.…”
Section: Earmentioning
confidence: 99%